Hamilton-Jacobi Theory and Moving Frames - MacArthur, J.D.; McLenaghan, R.G.; Smirnov, R.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The interplay between the Hamilton-Jacobi theory of orthogonal separation of variables and the theory of group actions is investigated based on concrete examples.